Bioactive chemical composition and pharmacological insights into Salvia species - Afzal, Tayyiba; Proćków, Jarosław; Łyczko, Jacek (Frontiers in Molecular Biosciences, 2025)
Salvia is a genus of Lamiaceae family with more than 1,000 species having diverse utility. The wide range of uses encompasses food, flavor, cosmetics, aromatherapy, horticulture, and medicine. It has been attributed to the presence of bioactive compounds belonging to essential oils, phenolic compounds, and flavonoids that are extensively studied using spectroscopic and chromatographic techniques. This review aims to investigate in-depth previously published literature from 2020 to 2025 on 59 Salvia species. It was performed with several key search words focused on the chemical compounds in Salvia spp. and their pharmacological efficacy. Salvia species were enriched with essential oils comprising important components: α-pinene, β-pinene, limonene, linalool, caryophyllene, germacrene, myrcene, α-thujone, and humulene. Potential health benefits owing to anticancer, antioxidant, antidiabetic, anti-inflammatory, antithrombotic, antirheumatic, and antiviral properties were reported from Salvia species. Salvia phytochemicals have been studied as regulating anticancer mechanisms at the cellular level by effectively modulating host cell responses in multiple ways. This review summarizes and discusses recent studies on the metabolite profiling of Salvia plants and bioactivities of the extracts and compounds. It may provide future perspectives on the in silico and pharmacognostic studies on potent Salvia compounds. Isolation and evaluation of bioactive compounds from the least studied species is recommended.